(untitled) (Journal of Social Sciences Review, 2023)
The research study finds the impact of COVID-19 on Small and Medium Enterprises (SMEs) in South Asian countries (excluding Afghanistan, due to the two-decades-long war on terrorism) by taking quarter-wise data from 2020 to 2021. By using the panel data random effect technique, the results demonstrate a negative relationship between COVID-19 spread and SMEs exports, as a one percent rise in the COVID-19 pandemic will result in a decline of 91 percent in exports of SMEs. The results also demonstrate that, with the exception of TTF (SME Financing as a % of Total Trade Finance), all explanatory variables are significant. SME Financing as a % of total trade finance (TTF) has a negative relationship with SMEs exports. Both BCS (Bank credit to SME sector) and NOB (percentage change in the number of SME borrowers) have a positive relationship with SMEE (Exports of SMEs), indicating that when BCS and NOB rise by one percent, SMEE will rise by .98 and 13.17 percent, respectively. The constant/intercept value shows that the SMEs exports will be 49.74 units when all other explanatory variables are set to zero. The research study also posed a policy recommendation in the situation of the COVID-19 epidemic, that what necessary and immediate action to be taken to save the lives and restore the economies of South Asian counties.